Cugoano on Redressing Slavery: The Demands of Liberty - Iziah C Topete (Journal of Modern Philosophy)
Quobna Ottobah Cugoano’s work from July 1787, Thoughts and Sentiments on the Evil and Wicked Traffic of the Slavery and Commerce of the Human Species, defended redressing transatlantic slavery on principled grounds. To elucidate the arguments that make Cugoano radical in his context, this article compares Cugoano with his abolitionist contemporary Thomas Clarkson. Clarkson developed a social contract theory, claiming that mentality endows all humans with liberty as a natural right. Clarkson argued that abolishing the slave trade would lead to emancipation naturally over time. Cugoano disagreed with piecemeal redress in Thoughts and Sentiments. Cugoano envisioned legal redress to necessitate that all Afro-diasporic laborers be enfranchised, securing the conditions for a free community. By examining his vision for liberation, the article reconstructs Cugoano’s idea of liberty as a social and common good. The social conception of liberty that Cugoano explores is an important contribution to the development of modern human rights.